Find $f'\left(2\right)$f′(2) if $f'\left(x\right)=4x^3-3x^2+4x-6$f′(x)=4x3−3x2+4x−6.

Easy

Approx a minute

Sign up to try all questions

Find $f'\left(4\right)$f′(4) if $f'\left(x\right)=\frac{\left(x^2-6\right)\times\left(2\right)+\left(2x\right)\left(2x\right)}{\left(x^2-6\right)^2}$f′(x)=(x2−6)×(2)+(2x)(2x)(x2−6)2.

By considering the graph of $f\left(x\right)=-6$f(x)=−6, find $f'\left(4\right)$f′(4).

By considering the graph of $f\left(x\right)=2x$f(x)=2x, find $f'$f′$\left(-5\right)$(−5).

Outcomes

M7-10

Apply differentiation and anti-differentiation techniques to polynomials